# Which equation could be used to find the perimeter of a rectangle that has a width of 12 cm and a length of 16 cm? a. P = 2 · 12 + 2 · 16 b. P = 2 · 12 + 16 c. P = 12 · 16 d. P = 12 + 16

QUESTION POSTED AT 05/12/2019 - 12:06 PM

QUESTION POSTED AT 05/12/2019 - 12:06 PM

It would be a. because a rectangle has 2 pairs of congruent sides so since the width is 12 and there are 2 sides with that measurement it would be 2(12) and the same goes for the length, and then you add them together.

**Answer:**

**A.** Less than 25.

**Step-by-step explanation:**

Let x represent 3rd side of triangle.

We have been given hat two sides of a triangle have lengths 10 and 15.

We will use triangle inequality theorem to find the 3rd side of the triangle. Triangle inequality theorem states that 3rd side of a triangle must be less than the sum of other two sides of triangle.

Using triangle inequality theorem, we can set following inequalities:

Therefore, the length of third side should be greater than 5.

**Therefore, the length of third side should be less than 25 and option A is the correct choice.**

ANSWERED AT 20/01/2020 - 01:47 PM

QUESTION POSTED AT 20/01/2020 - 01:47 PM

Let x = 3secβ, then dx = 3secβtanβ

∫dx/√(x²-9) = ∫[(3secβtanβ)/(3tanβ)]dβ

= ∫secβdβ

= ln |tanβ - secβ| + c

= ln |√(x² - 9)/3 - x/3| + C

= ln |√(x² - 9)/x| + C

∫dx/√(x²-9) = ∫[(3secβtanβ)/(3tanβ)]dβ

= ∫secβdβ

= ln |tanβ - secβ| + c

= ln |√(x² - 9)/3 - x/3| + C

= ln |√(x² - 9)/x| + C

ANSWERED AT 20/01/2020 - 01:46 PM

QUESTION POSTED AT 20/01/2020 - 01:46 PM

I'll try to explain. The trouble is that I do not know English :)

About Points

S = (x,y) searched point (it will be in the third quadrant )

M = (-2,0) Midpoint | SP |

P = (3,5) one end of the segment | SP |

You have to draw Cartesian.

we set in a point M and P. We both points by a simple and we extend it for the third quarter of the system. Compass measure the distance from the point M to the point P. From the point M we set a compass point S. Figure attached. Received point S = ( -7 , -5 ) . It sought a point that calculate .

We use the information that | SM | = | MP |

Answer : S = (-7,-5)

as soon as I had a good range will add drawing

About Points

S = (x,y) searched point (it will be in the third quadrant )

M = (-2,0) Midpoint | SP |

P = (3,5) one end of the segment | SP |

You have to draw Cartesian.

we set in a point M and P. We both points by a simple and we extend it for the third quarter of the system. Compass measure the distance from the point M to the point P. From the point M we set a compass point S. Figure attached. Received point S = ( -7 , -5 ) . It sought a point that calculate .

We use the information that | SM | = | MP |

Answer : S = (-7,-5)

as soon as I had a good range will add drawing

ANSWERED AT 20/01/2020 - 01:45 PM

QUESTION POSTED AT 20/01/2020 - 01:45 PM

First we need to define our conditions. Since the angles are complimentary, the sum of the angles must be equal to 90 degrees.

let x = first angle

y = second angle

x + y = 90

from the second condition in the problem

x + y =72 + x -y

solving for x

x= 54

therefore the shorter side is 90 - 54 = y

y = 36 degree, the shorter side

let x = first angle

y = second angle

x + y = 90

from the second condition in the problem

x + y =72 + x -y

solving for x

x= 54

therefore the shorter side is 90 - 54 = y

y = 36 degree, the shorter side

ANSWERED AT 20/01/2020 - 01:44 PM

QUESTION POSTED AT 20/01/2020 - 01:44 PM

The area would be 144 square inches. Solution:

Area of logo

Area = L x W

Area = 4 x 6

Area = 24 square inches

Area of Ads

Area = 6 x Logo

Area = 6 x 24

Area = 144 square inches

Area of logo

Area = L x W

Area = 4 x 6

Area = 24 square inches

Area of Ads

Area = 6 x Logo

Area = 6 x 24

Area = 144 square inches

ANSWERED AT 20/01/2020 - 01:44 PM

QUESTION POSTED AT 20/01/2020 - 01:44 PM

The coordinates of label 6 would be in (0,-5).

ANSWERED AT 20/01/2020 - 01:43 PM

QUESTION POSTED AT 20/01/2020 - 01:43 PM

Let x = width

x+12 = length

Perimeter of a rectangle, P = 2x+2(x+12) = 64

2x+2x+24=64

4x = 40

x=10

x+12 = 22

therefore, length is 22 in.

x+12 = length

Perimeter of a rectangle, P = 2x+2(x+12) = 64

2x+2x+24=64

4x = 40

x=10

x+12 = 22

therefore, length is 22 in.

ANSWERED AT 20/01/2020 - 01:41 PM

QUESTION POSTED AT 20/01/2020 - 01:41 PM

The equation can be obtained using microsoft excel, using manual substitution or using the statistics function of the calculator (I recommend Casio Fx 991-ES)

the equation that you will get from this method is initially

f(x) = y = -3x^2 - 4x + 5

converting this equation to the standard form, we obtain

Standard form: (x-h)^2 = -4a(y-k)

by completing the square

we can obtain

(x + 2/3)^2 = (-1/3)(y - 19/3)

you can recheck your answers by substituing the values

the equation that you will get from this method is initially

f(x) = y = -3x^2 - 4x + 5

converting this equation to the standard form, we obtain

Standard form: (x-h)^2 = -4a(y-k)

by completing the square

we can obtain

(x + 2/3)^2 = (-1/3)(y - 19/3)

you can recheck your answers by substituing the values

ANSWERED AT 20/01/2020 - 01:40 PM

QUESTION POSTED AT 20/01/2020 - 01:40 PM

Two figures are said to be congruent when they have the same shape and size or if one object is a mirror image of the other object.** I think, from the choices given, the best answer to illustrate that ABCD is congruent with PQRS is option B. Corresponding pairs of sides on ABCD and PQRS are equal in length.**

ANSWERED AT 20/01/2020 - 01:38 PM

QUESTION POSTED AT 20/01/2020 - 01:38 PM

Perimeter of a rectangle = 2L + 2W = 146

"width is 10 longer than twice the length"

translates to

W = 2L + 10

this can be rearranged to be

2L = W - 10

we can plug that into the first equation and get

(W - 10) + 2W = 146

add like terms

3W - 10 = 146

add 10 to both sides

3W = 156

divide both sides by 3

W = 52

therefore the width is**52 cm**

"width is 10 longer than twice the length"

translates to

W = 2L + 10

this can be rearranged to be

2L = W - 10

we can plug that into the first equation and get

(W - 10) + 2W = 146

add like terms

3W - 10 = 146

add 10 to both sides

3W = 156

divide both sides by 3

W = 52

therefore the width is

ANSWERED AT 20/01/2020 - 01:36 PM

QUESTION POSTED AT 20/01/2020 - 01:36 PM

**Answer:**

**=-**

**=.**

**Step-by-step explanation:**

Given, let be the angle in the III quadrant .

=-...... (given)

In III quadrant is negative and is positive .

because , =reciprocal of

it means , =

Therefore, first we find value of

We know that

∴

Now, we know that

therefore, first we find

Hence,** and **

ANSWERED AT 20/01/2020 - 01:33 PM

QUESTION POSTED AT 20/01/2020 - 01:33 PM

B. Months he runs. f(x) is the total number of miles he runs during each month. He starts with 0.5 miles and adds (+) 2 miles each month. Therefore, x must be the number of months. For example, month 1 (x) he runs 2.5 miles: 2.5 = 0.5 + 2(1); x=1.

ANSWERED AT 20/01/2020 - 01:33 PM

QUESTION POSTED AT 20/01/2020 - 01:33 PM

Not Answered Yet

ANSWERED AT 20/01/2020 - 01:32 PM

QUESTION POSTED AT 20/01/2020 - 01:32 PM

C.

2x-3y=6

-3y=6-2x

y=6/-3 -2/-3x

y= -2 + 2/3x

y=2/3x - 2

2x-3y=6

-3y=6-2x

y=6/-3 -2/-3x

y= -2 + 2/3x

y=2/3x - 2

ANSWERED AT 20/01/2020 - 01:31 PM

QUESTION POSTED AT 20/01/2020 - 01:31 PM

Sin-1 (3/5) = 36.869

cos 3/5 = 0.999

cos 3/5 = 0.999

ANSWERED AT 20/01/2020 - 01:30 PM

QUESTION POSTED AT 20/01/2020 - 01:30 PM

It is useful to start by drawing a picture to visualize this problem.

In this case we are going to use the trigonometric function cosine, which is Cos(theta) = adjacent / hypotenuse.

Cos(55) = 40 / x

After simplifying we reach the equation: X = 40 / cos(55)

which would then make the length of the wire 69.7 meters long.

In this case we are going to use the trigonometric function cosine, which is Cos(theta) = adjacent / hypotenuse.

Cos(55) = 40 / x

After simplifying we reach the equation: X = 40 / cos(55)

which would then make the length of the wire 69.7 meters long.

ANSWERED AT 20/01/2020 - 01:28 PM

QUESTION POSTED AT 20/01/2020 - 01:28 PM

I know the equation is 1/cos

but is it negative sqrt(3)/2 or positive?

or is it negative 1/2 or positive?

This makes the reference angle π/6 or 30º which gives cos 30º=√3/2 or a sec value of 2/√3=2√3/3

sec(-5pi/6)=-2√3/3

but is it negative sqrt(3)/2 or positive?

or is it negative 1/2 or positive?

This makes the reference angle π/6 or 30º which gives cos 30º=√3/2 or a sec value of 2/√3=2√3/3

sec(-5pi/6)=-2√3/3

ANSWERED AT 20/01/2020 - 01:27 PM

QUESTION POSTED AT 20/01/2020 - 01:27 PM

Use ^ to show exponents, example, 4^2 to show 4 to the power of 2

square root both sides

√x² + √16

x+4 is fully factored

square root both sides

√x² + √16

x+4 is fully factored

ANSWERED AT 20/01/2020 - 01:25 PM

QUESTION POSTED AT 20/01/2020 - 01:25 PM

Hello,

a(2)=-6

a(3)=-6*r

a(4)=-6*r²

a(5)=-6*r^3=162

a(5)/a(2)=r^3=162/(-6)=-27==>r=-3

a(1)=-6/(-3)=2

a(2)=2*(-3)

a(3)=2*(-3)²

a(4)=2*(-3)^3

a(5)=2*(-3)^4

a(n)=2*(-3)^(n-1)

Answer

a(2)=-6

a(3)=-6*r

a(4)=-6*r²

a(5)=-6*r^3=162

a(5)/a(2)=r^3=162/(-6)=-27==>r=-3

a(1)=-6/(-3)=2

a(2)=2*(-3)

a(3)=2*(-3)²

a(4)=2*(-3)^3

a(5)=2*(-3)^4

a(n)=2*(-3)^(n-1)

Answer

ANSWERED AT 20/01/2020 - 01:24 PM

QUESTION POSTED AT 20/01/2020 - 01:24 PM

Hello,

5<10+x ==> -5<x realized

10<5+x ==> x>5

x<5+10 ==> x<15

==> 5<x<15

==>x=6 or x=11 but for x=11 angle none obtus

==> 1solution x=6 (angle = 130.5416...°)

5<10+x ==> -5<x realized

10<5+x ==> x>5

x<5+10 ==> x<15

==> 5<x<15

==>x=6 or x=11 but for x=11 angle none obtus

==> 1solution x=6 (angle = 130.5416...°)

ANSWERED AT 20/01/2020 - 01:23 PM

QUESTION POSTED AT 20/01/2020 - 01:23 PM

**Answer:**

**Option B is correct that is the expression is equivalent, but it is not completely factored.**

**Step-by-step explanation:**

We have given an expression

when we take the common factor out which is 3 from the expression we will get

This expression is equivalent but is not completely factored because the term

**Hence, Option B is correct.**

Option C and D are discarded because given factor is equivalent

Option A is discarded because expression is not completely factored.

ANSWERED AT 20/01/2020 - 01:22 PM

QUESTION POSTED AT 20/01/2020 - 01:22 PM

Hello,

f(-3)=(-3)²-3*(-3)-7=9+9-7=11

Answer C

f(-3)=(-3)²-3*(-3)-7=9+9-7=11

Answer C

ANSWERED AT 20/01/2020 - 01:21 PM

QUESTION POSTED AT 20/01/2020 - 01:21 PM

To get the average resting position of the spring, we must subtract the minimum from the maximum height of the spring with respect to the floor.

So,

7 + (4/12) - [ 6 + (2/12) ] = 1.5 ft

Half of this is where the resting position of the spring is located with respect to the minimum height. If the resting position of the spring is set at 0, then the amplitude of the wave is:

A = 1.5 / 2 = 0.75

Since it takes 2 seconds for the spring to expand from minimum to maximum,

Period = 2 = 2π / n

n = π

The cosine function is:

y = A cos nt

where y is the distance from the resting position and t is the time in seconds.

y = 0.75 cos πt

So,

7 + (4/12) - [ 6 + (2/12) ] = 1.5 ft

Half of this is where the resting position of the spring is located with respect to the minimum height. If the resting position of the spring is set at 0, then the amplitude of the wave is:

A = 1.5 / 2 = 0.75

Since it takes 2 seconds for the spring to expand from minimum to maximum,

Period = 2 = 2π / n

n = π

The cosine function is:

y = A cos nt

where y is the distance from the resting position and t is the time in seconds.

y = 0.75 cos πt

ANSWERED AT 20/01/2020 - 01:21 PM

QUESTION POSTED AT 20/01/2020 - 01:21 PM

Hello,

Answer C

Be carefull

A: is (gof)(x)=g(f(x))=g(x^8)=6x^8-14

C: fog(x)=f((g(x))=f(6x-14)=(6x-14)^8

Answer C

Be carefull

A: is (gof)(x)=g(f(x))=g(x^8)=6x^8-14

C: fog(x)=f((g(x))=f(6x-14)=(6x-14)^8

ANSWERED AT 20/01/2020 - 01:19 PM

QUESTION POSTED AT 20/01/2020 - 01:19 PM

Hello,

Both curves passes by the vertex

Answer C

Both curves passes by the vertex

Answer C

ANSWERED AT 20/01/2020 - 01:18 PM

QUESTION POSTED AT 20/01/2020 - 01:18 PM

The answer would be -2. It is computed as follows:

6x - 3 = 5x - 5

6x - 5x = -5 + 3

x = -2

6x - 3 = 5x - 5

6x - 5x = -5 + 3

x = -2

ANSWERED AT 20/01/2020 - 01:17 PM

QUESTION POSTED AT 20/01/2020 - 01:17 PM

Standard form for first one is

ax+by=c

6y-12=-3x

add 3x both sides

3x+6y-12=0

add 12

3x+6y=12

second one

distribute (don't forget double negative y)

10-2x+2y=3x+1

minus 3x both sides

10-5x+2y=1

minus 10 both sides

-5x+2y=-9

the equations are

3x+6y=12

-5x+2y=-9

ax+by=c

6y-12=-3x

add 3x both sides

3x+6y-12=0

add 12

3x+6y=12

second one

distribute (don't forget double negative y)

10-2x+2y=3x+1

minus 3x both sides

10-5x+2y=1

minus 10 both sides

-5x+2y=-9

the equations are

3x+6y=12

-5x+2y=-9

ANSWERED AT 20/01/2020 - 01:17 PM

QUESTION POSTED AT 20/01/2020 - 01:17 PM

**Answer: 21 inches **

**Step-by-step explanation: this answer is for edge.nuity**

ANSWERED AT 20/01/2020 - 01:16 PM

QUESTION POSTED AT 20/01/2020 - 01:16 PM

**Answer:**

Number of trials are 250.

**Step-by-step explanation:**

A researcher finds 15% of all commuters in a metropolitan area take the train to work.

The researcher polls 250 people in the area to ask them whether they take the train to work or not.

We have tell the number of trials for this binomial experiment.

Researcher will do 250 trials to confirm whether they take the train work and this irrespective of their response.

ANSWERED AT 20/01/2020 - 01:16 PM

QUESTION POSTED AT 20/01/2020 - 01:16 PM

Hello,

Answer C

23/33=0.69 69 69 .....

7/11=0.63 63 63 ....

Answer C

23/33=0.69 69 69 .....

7/11=0.63 63 63 ....

ANSWERED AT 20/01/2020 - 01:15 PM

QUESTION POSTED AT 20/01/2020 - 01:15 PM